Oral Levosimendan Increases Cerebral Blood Flow Velocities in Patients with a History of Stroke or Transient Ischemic Attack: A Pilot Safety Study - Matti Kivikko, MD, PhD; Mikko Kuoppamäki, MD, PhD; Lauri Soinne, MD, PhD; Stig Sundberg, PhD; Pasi Pohjanjousi, MSc; Juha Ellmen, PhD; Risto O. Roine, MD, PhD (Elsevier, 2015)
Background: Intravenous levosimendan is indicated for acute heart failure. The compound has shown promising beneficial effects in ischemic stroke models. Objective: We evaluated the efficacy and safety of oral levosimendan in patients with a history of cerebral ischemia. Methods: In a randomized, double-blind, placebo-controlled, parallel-group study, 16 patients with a history of ischemic stroke/transient ischemic attack received oral levosimendan in 5 escalating doses from 0.125 to 2.0 mg daily for 18-day intervals of each dose; 5 patients received placebo. Twenty-four-hour ambulatory ECG and cerebral blood flow velocities using transcranial Doppler ultrasound were recorded at baseline and at the end of each dosing period. Vasomotor reactivity was assessed via the breath holding index. In addition, plasma levels of N-terminal-pro-B-type natriuretic peptide (NT-pro-BNP) and the metabolites of levosimendan were determined. Results: Levosimendan induced an increase in cerebral blood flow velocities and a decrease in NT-pro-BNP compared with placebo. There was no significant effect on breath holding index. Doses ≥0.5 mg increased heart rate by 5 to 9 beats/min. The dose level of 2.0 mg exceeded the preset safety margin of ventricular extrasystoles per hour (ie, upper 90% CI of the ratio of levosimendan to placebo above 2) with an estimate of 3.10 (90% CI, 0.95-10.07). Conclusions: Oral levosimendan increases cerebral blood flow velocities and diminishes NT-pro-BNP levels in patients with earlier ischemic cerebrovascular event. Daily doses up to 1.0 mg were well tolerated, whereas the 2.0 mg dose level induced an increase in ventricular extrasystoles. ClinicalTrials.gov identifier: NCT00698763.